Elevated α-hydroxybutyrate dehydrogenase is associated with in-hospital mortality in non-ischemic dilated cardiomyopathy - Li, Xinyi; He, Wenfei; Zhang, Xiaonan; Shu, Fen; Liu, Yaoxin; Tan, Ning; Jiang, Lei (Frontiers in Cardiovascular Medicine, 2022)
Background: Previous study found that implantation of a cardioverter-defibrillator likely caused a worse prognosis in older patients with non-ischemic systolic heart failure. This suggests that more precise risk stratification is needed in elderly patients. We conducted a retrospective study to evaluate the association of α-hydroxybutyrate dehydrogenase (α-HBDH) with mortality during hospitalization in elderly patients with non-ischemic dilated cardiomyopathy (NIDCM). Methods: 1,019 elderly patients (age ≥60 years) diagnosed with NIDCM were retrospectively enrolled from January 2010 to December 2019. Univariate and multivariate analyses were showed to explore the relationship between α-HBDH and in- hospital death. Results: Patients in elevated α-HBDH group (>182 U/L) had a longer hospital stays and higher in-hospital mortality. Univariate logistics regression analysis showed that elevated α-HBDH was significantly related to mortality (OR: 7.004, 95% CI: 3.583 13.693, p<0.001). Receiver operator characteristic (ROC) curve analysis reflected that α-HBDH levels had excellent predictive power for in-hospital death (AUC=0.810, 95% CI: 0.745 0.876, p<0.001). After adjustment of age, serum creatine, albumin and LVEF, multivariate regression analysis validated the association of elevated α-HBDH with increased risk of in-hospital death (p<0.05). Conclusions: Elevated α-HBDH level is significantly related to in-hospital mortality in older patients with NIDCM.